1998
DOI: 10.1002/(sici)1096-9071(199804)54:4<271::aid-jmv6>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of HCV type 2a in saliva from intravenous drug users

Abstract: Paired serum and saliva samples were collected simultaneously from 50 intravenous drug users with serologically proven hepatitis C virus infection. The oral health of the volunteers was also assessed. Hepatitis C virus RNA was detected by nested PCR, employing primers from the 5' noncoding region. Positive PCR products were sequenced using the Sequenase PCR Product Sequencing Kit (Amersham Life Sciences). HCV RNA was detected in 33 (66%) of the 50 serum samples. HCV RNA was detected in 19 (57.6%) of the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Discrepancy between blood and saliva HCV genotypes was reported by Roy et al [7], in drug abusers; he found that genotype 2 was more prevalent in saliva samples from these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancy between blood and saliva HCV genotypes was reported by Roy et al [7], in drug abusers; he found that genotype 2 was more prevalent in saliva samples from these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of 38 publications reported100% HCV-RNA detection in saliva samples from HCV-positive patients [16,17,25,29,38]; however, only a few cases or only patients with sialoadenitis were considered in these studies, which may represent a caveat. When reports with sample sizes larger than 30 HCV-positive patients were considered separately, the broad variability of frequencies was evident, ranging from 0 to 66% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This variation in HCV-RNA detection frequencies in saliva samples may be due to the saliva sampling method used.…”
mentioning
confidence: 99%
“…Although HCV can enter the saliva via the gingival sulcus (Maticic et al 2001), this cannot be the sole route because HCV RNA has been found in the saliva of edentate patients (Roy et al 1998). An alternative mechanism for viral entry into saliva is active HCV replication in the salivary glands (Arrieta et al 2001).…”
mentioning
confidence: 99%
“…An alternative mechanism for viral entry into saliva is active HCV replication in the salivary glands (Arrieta et al 2001). This mechanism would explain the detection of different viral genotypes in the serum and saliva of individual patients (Roy et al 1998) and the existence of patients with HCV RNA-negative serum and HCV RNA-positive saliva (Harle et al 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation